Study on the influence of industrial structure optimization on water environment and economy: A case study of Changzhou city - Bu, Jiuhe; Zhang, Shuiling; Wang, Xuesong; Li, Chunhui; Wang, Xuan; Liu, Qiang; Xu, Xiangen; Wang, Xia (Frontiers in Earth Science, 2023)
Economic development and large amounts of industrial production have led to environmental deterioration. The assessment and prediction of water environment capacity (WEC) are crucial supports for water quality target management. Therefore, this study aims to improve WEC via changes in industrial structure and to analyze the economic changes. For this purpose, the economic efficiency (EE), water use efficiency (WUE) and water treatment efficiency (WTE) are estimated by the EE-SBM (slack-based measure)-DEA (data envelopment analysis) model. Based on the proposed model, industry is divided into three types; green enterprises, yellow enterprises and red enterprises. Meanwhile, yellow enterprises and red enterprises are the major supervision subjects, the spatial distribution of different environmental risks is identified. The WECs of the main canals are analyzed based on dynamic changes in industrial structure by integrating the 0-D and MIKE11 models. The results showed that, after the adjusting the industrial structure, the maximum added value of the WEC of chemical oxygen demand (COD), total nitrogen (TN), ammonia nitrogen (NH3-N) and total phosphorus (TP) is 1744.66 t/a, 536.14 t/a, 24.81 t/a and 4.16 t/a, respectively. The results show that the canals (R40, R41, R20, R19 and R17) are overloaded with pollutants and indicate that TN be included as a water environment quality assessment target. Furthermore, after the optimization of industrial structure, the loss of industrial output value is 174.44 million yuan, and the added value of environmental economy is 232.12 million yuan. The findings provide important technical support for achieving industrial upgrading and sustainable development.